Microfluidic 68Ga-labeling: a proof of principle study. Issue 17 (17th April 2018) - Pfaff, Sarah; Philippe, Cecile; Pichler, Verena; Hacker, Marcus; Mitterhauser, Markus; Wadsak, Wolfgang
Abstract : The 68 Ga-labeling of three representative precursors (DOTA-NOC, NODAGA-RGD(yk) and PSMA-11) was performed applying a microfluidic continuous flow device. Abstract : Positron emission tomography (PET) as a tool for molecular imaging of cancer has gained huge interest in the last few years. Gallium-68 is a popular PET nuclide due to its favorable characteristics, like advantageous half-life (68 min) and independency of a cyclotron on-site for its production. Accordingly, several 68 Ga-complexes for cancer imaging via PET have been made available during the last few years. In this work, 68 Ga-labeled compounds were synthesized applying a commercially available microfluidic device for the first time. Therefore, a proof of principle study using three important radiotracers, [ 68 Ga]Ga-PSMA-11, [ 68 Ga]Ga-NODAGA-RGDyk and [ 68 Ga]Ga-DOTA-NOC, was designed. For all three radioligands, various synthesis parameters were evaluated and the feasibility of using a continuous flow reactor was assessed. All of the precursors were successfully radiolabeled with a radiochemical yield higher than 80%, proving the principle that a microfluidic set-up is a suitable approach for the production of 68 Ga-labeled tracers.